A public service-dominant logic for the executive education of public managers. Issue 1 (March 2017) - Hiedemann, Alexander M; Nasi, Greta; Saporito, Raffaella
Building on the concept of Public Service-Dominant Logic (PSDL), this article aims to apply the public service-dominant logic to executive education. We argue that fit-for-purpose and effective executive master programs for public managers (EMPA) need to be designed from a public service perspective. Framing executive education as a service enables the enhancement of the effectiveness of public action as a result of inter-organizational capacity and the co-production of learning outcomes. This article is an invitation to teach what we write, to practise what we teach and to teach through practice, which is what a public manager attending an executive program would expect in terms of public service experience. PSDL was applied to the flagship program at SDA Bocconi School of Management for public sector managers in order to produce the first concrete contribution and to illustrate how switching from a product-logic to a service-logic can have a positive effect on executive education, its structure and curricula. By retrospectively applying PSDL in order to investigate any concrete outcome on revising executive education programs, we show that it is possible to generate a concrete impact in terms of participant satisfaction and the perceived long-term added value of the learning experience by focusing on the education outcome, meeting and anticipating the participants' needs and expectations, and considering the participants as active stakeholders at the heart of the delivery process.